Applications of a big data platform based on PaaS - Haiyong XU; Yan HUANG (Dianxin kexue)
As a platform of data storage,processing,and service,big data platform needs to support internal and external various big data applications.A solution applied PaaS technology to the big data platform was proposed.Details of the key technical solutions such as the architecture of PaaS cloud computing platform,hierarchical scheduling scheme,multi-tenant management and global scheduling of Hadoop tasks were described.It was proved that the platform could remarkably improve big data application development efficiency and help application deployment fast.In the meantime,good elastic scaling capability can effectively improve big data application system resource utilization.